Bibliometric analysis of traditional Chinese medicine for viral infections through immune modulation (2015–2025) - Zhang, Lei; Jin, Shuang; Qin, Chuang; Ma, DaBao; Ye, JinSheng; Liu, QingQuan (Frontiers in Immunology, 2025)
ObjectivesThe immunomodulatory properties of traditional Chinese medicine (TCM) have attracted significant attention as a strategy for addressing viral infections. However, a comprehensive bibliometric analysis is still lacking. This study aims to systematically identify research trends, knowledge hotspots, and emerging themes in TCM applications for viral infections through immune modulation from 2015 to 2025.MethodsWe collected publications from the Web of Science database from 2015 to 2025 and performed a comprehensive analysis using R, VOSviewer, and CiteSpace. In addition, clinical trial records published during this period were obtained from the PubMed database to assess clinical advancements in this field.ResultsA total of 3,370 publications were analyzed in this study. Between 2015 and 2021, the number of publications in this field showed two distinct stepwise increases, separated by a period of relative stability, followed by a modest decline from 2021 to 2025. China contributed the highest volume of publications and demonstrated the broadest international collaborations, establishing itself as the leading country in this area. Frontiers in Immunology published the largest number of articles, while the Journal of Virology was the most frequently cited journal. Core topics included “Infection,” “COVID-19,” “Expression,” “Antiviral,” and “Protein.” The primary research focus centered on TCM’s antiviral effects and its modulation of immune responses, investigating its regulatory impact on inflammation and cytokine storms during viral infections, and examining TCM’s role in modulating immune responses to viral vaccines. Clinical trials in this field focus on improving the management of viral infections, and immune reconstitution strategies for chronic infections.ConclusionThis study systematically analyzes the scientific literature in this field, providing valuable insights into current research trends and highlighting future directions in the application of TCM to the immunomodulation of viral infections.